Denture-Related Stomatitis Is Associated with Endothelial Dysfunction. (19th June 2014) - Maciąg, Joanna; Osmenda, Grzegorz; Nowakowski, Daniel; Wilk, Grzegorz; Maciąg, Anna; Mikołajczyk, Tomasz; Nosalski, Ryszard; Sagan, Agnieszka; Filip, Magdalena; Dróżdż, Mirosław; Loster, Jolanta; Guzik, Tomasz J.; et al.
Abstract : Oral inflammation, such as periodontitis, can lead to endothelial dysfunction, accelerated atherosclerosis, and vascular dysfunction. The relationship between vascular dysfunction and other common forms of oral infections such as denture-related stomatitis (DRS) is unknown. Similar risk factors predispose to both conditions including smoking, diabetes, age, and obesity. Accordingly, we aimed to investigate endothelial function and major vascular disease risk factors in 44 consecutive patients with dentures with clinical and microbiological features of DRS (n = 20 ) and without DRS (n = 24 ). While there was a tendency for higher occurrence of diabetes and smoking, groups did not differ significantly in respect to major vascular disease risk factors. Groups did not differ in main ambulatory blood pressure, total cholesterol, or even CRP. Importantly, flow mediated dilatation (FMD) was significantly lower in DRS than in non-DRS subjects, while nitroglycerin induced vasorelaxation (NMD) or intima-media thickness (IMT) was similar. Interestingly, while triglyceride levels were normal in both groups, they were higher in DRS subjects, although they did not correlate with either FMD or NMD. Conclusions . Denture related stomatitis is associated with endothelial dysfunction in elderly patients with dentures. This is in part related to the fact that diabetes and smoking increase risk of both DRS and cardiovascular disease.